Comparative analysis of life cycle greenhouse gas emission of passenger cars: A case study in China. (15th February 2023) - Zhang, Haoyi; Zhao, Fuquan; Hao, Han; Liu, Zongwei
Abstract: Greenhouse gas emission is a vital problem affecting the fate of mankind. To reduce the emission, passenger cars with various types of power system has been introduced in China. However, there is an uncertainty that whether these vehicles can reduce greenhouse gas emissions and how much emissions can be reduced, especially in terms of life cycle aspect. In this paper, a calculation method has been established to study their life cycle carbon emissions, with consideration of various power system, model class and electric driving range. It is found that most NEVs and Hybrid Electric Vehicle (HEVs) have emission reduction effects compared to internal combustion engine vehicles (ICEVs). The emission reduction rate of vehicles is between 6.56% and 44.4% in 2020, 13.97%–53.39% in 2025 and 19.65%–57.49% in 2030. It is also found that this reduction rate is significantly different between different vehicle class, power system and electric driving range. Battery electrical vehicle (BEVs) in 2020 with electric driving range over 700 km are even worse in carbon emission, the worst is −33.08%. The results could be useful for GHG emission prediction and power system selection for companies. Policies can be formulated to guide enterprise choosing power system with lower carbon emission. Highlights: List three main factors influencing the life cycle carbon emissions of passenger car. Analyze the sensitivity of various vehicle models to three influencing factors. Analyze the carbon reduction effect of three main factors between 2020 and 2030.